3MnGO Application / Muhammad Alif Ifdam Jafrudin, Wan Noor Aziemah Wan Mohd Fouzi and Norzaharah Abdul Wahab - Jafrudin, Muhammad Alif Ifdam; Wan Mohd Fouzi, Wan Noor Aziemah; Abdul Wahab, Norzaharah (2022)
The hospitality and tourism industry is a large industry that encompasses all economic activities related to travel and tourism include in Malaysia too. As we know, technology is growing rapidly all over the world and everyone using smartphones allows everyone to surf the internet or use the app at the fingertips anywhere at any time because inside every smartphone there should be an app that can be downloaded on their own or that is already in the smartphone. Our aim is to help and promote local traders and travel agencies that are affected by the pandemic and enhance their lifestyles to become better as well as promoting interesting destinations in Malaysia. The different about our app with other travel app is the users can make choices between custom packages or existing packages, for custom packages, users can choose their own destinations, accommodations, restaurants, mosques, local souvenir sellers/ shops, and types of transportation. Then, for the existing packages, the users can choose their own preferred travel agencies from any states they wish to travel to. Hence, our app is very easy to use and user friendly, anyone from any range of ages can use the app and it will be convenient for traveller to choose their preferred destinations. In conclusion, this app is to attract more foreign tourists to explore Malaysia easily with the 3MnGo app.